Pengaruh Komitmen Profesional Terhadap Independensi Auditor Dengan Moderasi Budaya Etis Organisasi Dan Pengawasan Internal Di Kantor Akuntan Publik - Riana Anggraeny Ridwan; Nur Alimin Azis (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the influence of professional commitment on auditor independence, as well as investigate the role of auditor emotional intelligence and internal supervision in Public Accounting Firms as moderation variables. The research sample consists of 107 public auditors in Indonesia who will be active in 2024, with a simple random sampling technique. Data was collected through a questionnaire survey method. The results of the analysis show that professional commitment has a positive effect on the independence of auditors. In addition, auditors' emotional intelligence strengthens the relationship, as well as effective internal oversight of the KAP has been shown to strengthen the influence of professional commitment on auditor independence. These findings affirm the importance of strengthening the emotional capacity of individual auditors as well as the development of internal oversight systems within organizations as part of efforts to maintain auditors' independence and professionalism in audit practice.